University students’ lived experiences of blogging as a tool for writing: A hermeneutic phenomenological exploration in the Bangladeshi context - Easir Arafat; Nashrah Sharfuddin; John Paul Shimanto Sarkar; Tarannum Fatema Chowdhury (International Journal of Educational Research Open)
This hermeneutic phenomenological study explored the lived experiences of Bangladeshi university students using blogging as a writing tool. Semi-structured interviews were conducted with 20 students from public and private universities who were actively engaged in blogging as part of their English Composition coursework. Participants had varying levels of prior experience with blogging, ranging from beginners to those with up to three years of experience. This study employed the Social Cognitive Theory as its theoretical framework and data analysis was guided by the hermeneutic circle, investigator triangulation, and thematic analysis. Four key themes emerged: (1) Discovering the Joy of Writing, capturing the emotional fulfillment and creative exploration that blogging enables; (2) Skill Development and Confidence, referring to the gradual improvement in writing skills and self-assurance; (3) Autonomy and Ownership in Writing, emphasizing the control, creativity, and personal responsibility writers experience in shaping their work; and (4) Navigating Challenges and Fostering Community, exploring how overcoming obstacles can contribute to building a supportive writing community. The findings suggest that blogging holds significant pedagogical potential by fostering interactive learning, self-reflection, and writing experimentation. However, its successful integration into writing curricula requires addressing socio-cultural and infrastructural challenges specific to the Bangladeshi context. The findings also highlight the potential for Bangladesh to serve as a valuable reference point for other developing nations exploring the integration of blogging into writing instruction.